Financial inclusion in the digital era: a key driver for reducing income inequality - Li, Zaiyang; Lunku, Hassan Swedy; Yang, Shaohua (Technological and Economic Development of Economy, 2025)
Growing income inequality remains a pressing phenomenon in many developing economies, especially Sub-Saharan Africa (SSA), and may cause discontent in achieving inclusive growth which is crucial for sustainable development. Economies turning to financial inclusion as a critical component of economic development where access to formal financial institutions and services remains limited in the region. Digital technology has the potential to advance financial inclusion by tapping technology to extend financial access to underserved populations, as lack of access to efficient financial products and services can perpetuate income disparities. We employ a generalized quantile regression with an instrumental variables framework to investigate the distributional effects of financial inclusion and digitalization on income inequality in the region. Results imply that the use and adoption of the internet and mobile phones contribute to reducing income inequality, highlighting the transformative potential of digitalization across different quantiles. The findings indicate that public expenditure favors distributional impacts on inequality across quantiles. Our study suggests that policymakers in the region should prioritize the adoption and use of digital technology and foster an enabling policy that encourages the development of digital infrastructure and financial services to ensure widespread access and benefits for all segments of the population.First published online 18 February 2025